2023
DOI: 10.3389/fonc.2023.1124520
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibroblast growth factor 18 in cancers: functions and signaling pathways

Abstract: Fibroblast growth factor 18(FGF18) is a member of the fibroblast growth factor family (FGFs). FGF18 is a class of bioactive substances that can conduct biological signals, regulate cell growth, participate in tissue repair and other functions, and can promote the occurrence and development of different types of malignant tumors through various mechanisms. In this review, we focus on recent studies of FGF18 in the diagnosis, treatment, and prognosis of tumors in digestive, reproductive, urinary, respiratory, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 209 publications
0
0
0
Order By: Relevance
“…No reuse allowed without permission. cancers, including colorectal, ovarian, and gastric cancers [9]. Sonvilla et al showed that FGF18 expression is elevated in colorectal tumors and promotes tumor cell growth by enhancing the proliferation of colon-associated fibroblasts as well as tumor cells and neovascularization [10].…”
Section: Introductionmentioning
confidence: 99%
“…No reuse allowed without permission. cancers, including colorectal, ovarian, and gastric cancers [9]. Sonvilla et al showed that FGF18 expression is elevated in colorectal tumors and promotes tumor cell growth by enhancing the proliferation of colon-associated fibroblasts as well as tumor cells and neovascularization [10].…”
Section: Introductionmentioning
confidence: 99%